Reaffirming Javanese Patriarchy: Gender Roles and Cultural Identity in K.H. Bisri Musthafa’s Tafsīr al-Ibrīz - Arinda Rosalina; Anwar Mujahidin (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2025)
This research examines the intersection between Qur'anic interpretation and Javanese culture, focusing on K.H. Bisri Musthafa’s Tafsīr al-Ibrīz, a commentary written in Javanese using pegon script. The study employs an in-depth analytical approach, addressing two key aspects: the representation of verses concerning gender relations (men and women), and the dynamic interplay between the interpreter’s perspective and the Javanese cultural framework. As a library-based study, this research adopts a descriptive-analytical method, utilizing hermeneutic theory to analyze the triad of text, interpreter, and socio-cultural context. The findings reveal that al-Ibrīz positions men as the leaders of the household, asserting their authority over women, who are expected to submit to male guardianship. The commentary emphasizes biological determinism: men are portrayed as physically strong and resilient, thus assigned the role of providers and protectors, while women are associated with gentleness and confined to domestic spheres—summarized in the Javanese culture as macak (grooming), masak (cooking), and manak (childbearing). Additionally, the interpretation highlights women’s reproductive functions, including menstruation, menopause, and breastfeeding obligations. The analysis confirms a cultural-textual synergy: the interpreter’s model aligns with traditional Javanese patriarchy, where men dominate household governance, and women occupy a subordinate position. REFERENCES Abu Syuqqah, Abdul Halim. Women's Freedom. Cet. 1. Jakarta: Echoes of Human Press, 1997. Amrullah et al., Najib.